PENGEMBANGAN LITERASI KHUTBAH BERBASIS TURATS YANG RAMAH BAGI LINGKUNGAN, NEGARA, DAN MINORITAS DI PONDOK PESANTREN SABILURROSYAD GASEK KOTA MALANG JAWA TIMUR - Anas, Mohamad; Zakiyah, Millatuz; Rahman, Khalid; Fitrianita, Titi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Religious Podium as a Mercy for the Universe: Development of Turats Based on Literacy that is Friendly to the Environment, Country, and Minorities at the Sabilurrosyad Gasek Islamic Boarding School, Malang City, East Jawa. Khutbah Jumat is a mandatory weekly agenda for male Muslims who have reached puberty, but in fact Khutbah Jumat as a series of Friday prayers has not been able to act as an effective medium of da'wah. This da'wah media is sometimes not used optimally. The religious podium that is embodied in Khutbah Jumat as an obligatory worship service can be a source of mercy for the universe, not only for Muslims, but also for minorities, environment, even on health, economic and state issues with a humanist and peaceful narrative. The method of implementing this community service activity is socialization and literacy workshops based on turats that are friendly for environment, the country, and minorities with participants from the Gasek Islamic Boarding School students in Malang, East Java. The Muslim community has high trust in the authority of houses for worship as religious educational institutions. Based on the results of the community service activity, it can be explained the preparatory community service was not found responsive Khutbah Jumat for contemporary issues, diversity, environment, and gender. These findings have led us to develop the curriculum of Khutbah Jumat for humanity and responsive to contemporary issues and publish turats based on literacy that is friendly to environment, the state, and minorities